2010
DOI: 10.1590/s0100-72032010001200008
|View full text |Cite
|
Sign up to set email alerts
|

Pré-eclâmpsia: estresse oxidativo, inflamação e disfunção endotelial

Abstract: Preeclampsia is a systemic syndrome characterized by inflammatory and antiangiogenic states. The pathogenesis of preeclampsia involves deficient trophoblast invasion that is responsible for altered uterine blood flow and placental oxidative stress. The damaged placenta produces higher concentrations of sFlt-1, a soluble receptor for VEGF and PlGF that is released in the maternal circulation and is involved in endothelial dysfunction. Actually, all processes involved in inflammation, endothelial dysfunction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 39 publications
0
19
0
3
Order By: Relevance
“…Preeclampsia is a systemic disease characterized by intense inflammatory response, endothelial injury, platelet aggregation, coagulation system activation and increase vascular resistance. It affects about 5–8% of all pregnant women [1] [3] . The diagnosis of preeclampsia is based on the development of hypertension (≥140/90 mmHg) and significant proteinuria (≥300 mg/24 hours) after 20 weeks of gestation [4] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preeclampsia is a systemic disease characterized by intense inflammatory response, endothelial injury, platelet aggregation, coagulation system activation and increase vascular resistance. It affects about 5–8% of all pregnant women [1] [3] . The diagnosis of preeclampsia is based on the development of hypertension (≥140/90 mmHg) and significant proteinuria (≥300 mg/24 hours) after 20 weeks of gestation [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Despite its relevance, preeclampsia pathogenesis is not completely understood. It has been established that the trophoblast has a key role in this process and many other conditions related to chronic inflammation can be relevant in different stages of the disease [3] .…”
Section: Introductionmentioning
confidence: 99%
“…A disorder associated with hypertension and proteinuria starting on the 20th week of pregnancy (38), preeclampsia has a significantly heightened inflammatory response in which the inflammasome plays a contributing role (39). In regards to inflammasome regulation in preeclampsia, Weel and colleagues showed that the NLRP3 inflammasome is upregulated, and that it contributes to the damaging effects of inflammation present in preeclampsia (29), a finding that was then corroborated by Stodle et al who showed that cholesterol and uric acid crystals activated the NLRP3 inflammasome in preeclampsia (30).…”
Section: Preeclampsia and Placental Inflammationmentioning
confidence: 99%
“…They express only HLA-G, HLA-C and HLA-E. Saito, Sakai, Sasaki, Nakashima and Shiozaki (2007) demonstrated reduction in the percentage of regulatory T cells in patients with preeclampsia; this would lead to increased activation of lymphocytes and thus, greater inflammatory response. Therefore, one can infer that the breakdown of maternal-fetal or maternal-placental tolerance could lead to deficient placentation, inflammatory response and, consequently, to preeclampsia (Oliveira, Karumanchi, & Sass, 2010).…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%